Shipping noise assessment in the Black Sea: insights from large-scale ASI CeNoBS survey data - Frassà, Veronica; Prospathopoulos, Aristides M.; Maglio, Alessio; Ortega, Noelia; Paiu, Romulus-Marian; Azzellino, Arianna (Frontiers in Marine Science, 2023)
Sighting data deriving from the ACCOBAMS1 Survey Initiative (ASI), conducted through the CeNoBS2 project, enabled the investigation of the habitat preferences for three different cetacean subspecies occurring in the Black Sea waters: the bottlenose dolphins (Tursiops truncatus), the common dolphins (Delphinus delphis) and the harbour porpoise (Phocoena phocoena). ASI aerial surveys, aiming at assessing the distribution and abundance of cetacean populations, were conducted during summer of 2019 in waters in front of Romania, Georgia, Bulgaria, Turkey and Ukraine. The surveys allowed recording of 1716 sightings: 117 bottlenose dolphins, 715 common dolphins and 884 harbour porpoises. The aim of this study was twofold: (i) to develop habitat models, using physical characteristics, such as depth and slope, as covariates, in order to estimate the presence probability of the three cetacean species in the Black Sea; (ii) to demonstrate the usefulness of the habitat models in support of environmental status assessments on marine mammals where the stressor is the shipping noise. The results of this study show the reliability of physical covariates as predictors of the probability of occurrence for the three species of interest in the Black Sea, providing additional knowledge, complementary to abundance estimates, which may support the assessment of the vulnerability of marine areas to different pressures, including noise.